An Analysis of Management Wisdom on Occupational Health and Safety at Tanjung Pura Hospital, Langkat District – 2018 - Yusuf, Muhammad; Ketaren, Otniel; Dachi, Rahmat Alyakin (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
The result of a preliminary survey by the writer found that Tanjung Pura Hospital not yet implemented and a team for Occupational Health and Safety. Whereas, that was stated in ministry regulation at number PERMENKES 66/2016 and has to prove it with the absence of report due to occupational health and safety cases in Tanjung Pura Hospital. Based on the background, this study aimed to analyze the management wisdom on occupational health and safety. This study used the qualitative method with case study design. To collect the data the writer used interviews with several informants, that is Director of Tanjung Pura Hospital, Head of Division, Quality Team, and Occupational Health and Safety’s Team. The result of the study found that the regulation of occupational health and safety in Tanjung Pura Hospital not formed yet. In another hand, the planning and also the implementation process of monitoring and evaluation of occupational health and safety not worked. In conclusion, all the wisdom of occupational health and safety at Tanjung Pura Hospital not operated, and this study should be the basis to implement the ministry regulation PERMENKES 66/2016.